Comparative study on using carbera odollam oil and palm oil for microbial lipase production / Mohd Zulhilmi Wan Salleh - Wan Salleh, Mohd Zulhilmi (2013)
Research on useful application of Cerbera odollam in Malaysia is relatively few despite its abundance mainly due to its toxicity. In order to utilize this plenty natural resource, the Cerbera odollam oil was extracted from the fruit's seed. The yield from the extracted oil achieved was at 53% (w/w) oil. On the other hand, bacteria known as Pseudomonas aeruginosa ATCC 27853 was able to grow in the agar medium containing Cerbera odollam as base media. This finding led to the use of this microbe to enhance lipase production by Cerbera odollam oil as a carbon source in the fermentation media. Similar fermentation using palm oil was carried out as comparison. There has been found that 3% (v/v) of oil produced maximum activity for media of Cerbera odollam oil compared to 5% (v/v) optimum of palm oil with activity 199 mU/mL and 189 mU/mL respectively. Lipase production secreted high activity when initial pH 7 was applied and the maximum activity achieved was 199 mU/mL and 134 mU/mL for Cerbera odollam media and palm oil media respectively after incubation of 72 hour. The temperature of 37°C was found as the optimum condition with activity 200 mU/mL and 146 mU/mL for Cerbera odollam oil media and palm oil media respectively. Other study showed that lipase activity from both produced media was found to be stimulated by the addition of ion Ca2+, Cu2+, Li+, and Mn2+ only stimulated palm oil produced media. The optimum conditions by response surface methodology revealed that the maximum activity for Cerbera odollam oil production media is 219 mU/mL for optimum condition at 44°C, 3.4% (v/v) of Cerbera odollam oil and at 55 hour. Furthermore, the maximum of lipase activity of210.76 mU/mL has been produced by Palm oil production media at optimum condition of 46.3°C, with concentration 6.3%(v/v) of palm oil and at 48.6 hour.